Resolution of a Diplomatic Blockade through Multi-Track Diplomacy: A Case Study of Qatar’s Foreign Policy amid its Diplomatic Blockade - Munir, Aniqa; Khan, Muhammad Farhan; Jamshaid, Muhammad (Pakistan Languages and Humanities Review, 2024)
The purpose of this study is to highlight all such restrictions tapping on a state as a tool of diplomacy, done by other states to achieve their self-interests, can be resolved by using different tracks of diplomacy while conducting foreign policy of the state. The most important objective of this research is to establish that different tracks of diplomacy can be adopted to successfully survive a diplomatic blockade. A state can endure a diplomatic blockade by following different tracks of diplomacy in an independent foreign policy. Qatar’s diplomatic blockade is taken as a case study in this research. It is observed that Qatar successfully overcame its diplomatic blockade from 2017 to 2021. This blockade was imposed by some Middle Eastern states.The research approach for the stated issue includes descriptive nature. Primary as well as secondary data sources are used in this research which include research articles, books, observations, newspaper reports, official government statements, and written content. This paper institutes that the modern tools and techniques of diplomacy can help resolve any sudden crisis in an amicable way by applying the means of Multi-track diplomacy.